Indian Ocean: Global and Regional Strategies - Iram Khalid (Journal of Political Studies, 2013)
The term Indian Ocean States is applied to both coastal and landlocked states. In the connection total 51states are remained under discussion in the Indian Ocean strategies. Their issues and problems are diverse. These issues have made the India Ocean an area of conflict. The wealth and the resources of the Indian Oceans have significantly involved the extra regional actors in the ocean. The present study focuses that this involvement of extra regional actors and the competition between the regional powers has shaped the policies and designs of global political settings regarding Indian Ocean. The study concludes that, Politics and strategies are an ongoing phenomena but the reality is that Indian Ocean is having the name of the India but is not totally in Indian control and custody. In this world of power and competition things and patterns keep on changing hence the command of Oceans. The changing power pattern round the globe is affecting the politics of Indian Oceans.